Mobile Devices in Indonesian Language Learning on Multi Graders at Elementary Schools - Ferril Irham Muzaki (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
The objectives of this study were (1) to measure the transformation of mobile learning devices in elementary schools in multi grade classes, (2) to examine the visibility of the development of Podcast devices for Indonesian language learning in multi grade elementary schools and (3) to assess the probability of using video technology tools on demand (VOD) on Indonesian language learning in elementary schools in multi grade classes. The method used is ethnographic study with triangulation of data in the form of interviews, the results of observations and technology assessment for Indonesian language learning in multi grade-based elementary schools using Mobile devices. The results of this study are (1) Mobile learning devices, especially television can be used for multi grade learning, (2) podcast device development also has the opportunity to be further developed, and (3) tools for learning are more related to the process of developing mobile devices in schools basic. Conclusions from this study, the development of Mobile devices for Indonesian Language in Elementary Schools needs to be done, taking into account the visibility of the learning device. It is recommended to the stakeholders to optimize the Indonesian Language device for multi grade class.